Diet-induced dyslipidemia induces metabolic and migratory adaptations in regulatory T cells. Issue 5 (11th July 2020) - Amersfoort, Jacob; Schaftenaar, Frank H; Douna, Hidde; van Santbrink, Peter J; van Puijvelde, Gijs H M; Slütter, Bram; Foks, Amanda C; Harms, Amy; Moreno-Gordaliza, Estefania; Wang, Yanyan; Hankemeier, Thomas; Bot, Ilze; et al.
Abstract: Aims: A hallmark of advanced atherosclerosis is inadequate immunosuppression by regulatory T (Treg) cells inside atherosclerotic lesions. Dyslipidemia has been suggested to alter Treg cell migration by affecting the expression of specific membrane proteins, thereby decreasing Treg cell migration towards atherosclerotic lesions. Besides membrane proteins, cellular metabolism has been shown to be a crucial factor in Treg cell migration. We aimed to determine whether dyslipidemia contributes to altered migration of Treg cells, in part, by affecting cellular metabolism. Methods and results: Dyslipidemia was induced by feeding Ldlr −/− mice a western-type diet for 16–20 weeks and intrinsic changes in Treg cells affecting their migration and metabolism were examined. Dyslipidemia was associated with altered mTORC2 signalling in Treg cells, decreased expression of membrane proteins involved in migration, including CD62L, CCR7, and S1Pr1, and decreased Treg cell migration towards lymph nodes. Furthermore, we discovered that diet-induced dyslipidemia inhibited mTORC1 signalling, induced PPARδ activation and increased fatty acid (FA) oxidation in Treg cells. Moreover, mass-spectrometry analysis of serum from Ldlr −/− mice with normolipidemia or dyslipidemia showed increases in multiple PPARδ ligands during dyslipidemia. Treatment with a synthetic PPARδ agonist increased the migratory capacity of Treg cells in vitro and in vivo in an FA oxidation-dependent manner. Furthermore, diet-induced dyslipidemia actually enhanced Treg cell migration into the inflamed peritoneum and into atherosclerotic lesions in vitro . Conclusion: Altogether, our findings implicate that dyslipidemia does not contribute to atherosclerosis by impairing Treg cell migration as dyslipidemia associated with an effector-like migratory phenotype in Treg cells. Graphical Abstract: